POTENCIAIS FOTOPROTETOR E ANTIOXIDANTE DE BLENDS DE CHÁS - DA ROSA, Juliano Santos,; DE CASTRO, Thiago Luis Aguayo,; MASCARENHAS, Maria do Socorro,; CARDOSO, Claudia Andrea Lima Cardoso, (ANAIS DO ENIC, 2024)
-